STUDI MENGENAI KEPUTUSAN PEMBELIAN DENGAN PENDEKATAN SERVICE ENCOUNTER, SERVICE CONVENIENCE DAN PRODUCT KNOWLEDGE YANG DIMEDIASI OLEH PURCHASE INTENTION PADA BENGKEL PT. ASTRA INTERNATIONAL-DAIHATSU SALES OPERATION SEMARANG - Sumarno, Sumarno; Soesanto, Harry; Sufian, Syuhada (Master of Management Diponegoro University, 2016)
This research was conducted in workshop PT. AstraInternational-DaihatsuSales Operation,Semarang branch. Started from a finding which showed an indication that the consumer’s decision to utilize the service of workshop PT. AstraInternational-DaihatsuSales Operation Semarang branch is still low. The objective of this research was to analyze the effect of service encounter, service convenient and product knowledge on purchase intention and purchase decision.The approach in this research involved five variables, namely service encounter, service convenience, product knowledge and purchase intention that can allegedly explain the low purchase decision of services of workshop PT. AstraInternational-DaihatsuSales Operation Semarang branch. The analysis of this research used Structural Equation Modeling method.The results showed that service encounter, service convenience and product knowledge proved positive and significant effect on purchase intention and purchase decision. While purchase intention had negative but not significant effect on purchase decision.